2019
DOI: 10.2147/ott.s233868
|View full text |Cite
|
Sign up to set email alerts
|

<p>Primary Prostatic Extra-Gastrointestinal Stromal Tumor Treated with Imatinib Mesylate as Neoadjuvant and Adjuvant Therapy: A Case Report and Literature Review</p>

Abstract: The current study presents a case of primary prostatic extra-gastrointestinal stromal tumor (EGIST) in a 43-year-old man who suffered acute urinary retention. The serum level of prostate-specific antigen was normal. Imaging examinations demonstrated a diffusely enlarged prostate compressing the rectum without evidence of metastasis. After excluding the possibility of secondary involvement by a rectal GIST, the pathologic diagnosis of primary prostatic EGIST was established based on microscopic study, immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Rarely seminoma 8,11,16,21 and a single case of adrenal neuroblastoma were reported 19 . Additional 52 articles included case reports of the association (Table 3) 2,3,5,24-55 , or a primary genitourinary organ GIST (Table 4) [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] .…”
Section: Resultsmentioning
confidence: 99%
“…Rarely seminoma 8,11,16,21 and a single case of adrenal neuroblastoma were reported 19 . Additional 52 articles included case reports of the association (Table 3) 2,3,5,24-55 , or a primary genitourinary organ GIST (Table 4) [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] .…”
Section: Resultsmentioning
confidence: 99%
“…Considering EGISTs are not sensitive to conventional chemotherapy and radiotherapy, imatinib mesylate is proposed as adjuvant therapy for advanced, unresectable, and metastatic cases. As a tyrosine kinase inhibitor of c-kit and PDGFRA, imatinib mesylate has been proven to be an effective therapy for GISTs and EGISTs 13 . Tumor size and mitotic activity have been reported as significant prognostic factors, which should be considered for precise risk stratification and classification.…”
Section: Discussionmentioning
confidence: 99%
“…Since Van Der Aa et al. 3 reported the first case of primary prostatic EGIST in 2005, only 14 cases 3 16 in the English language appear in PubMed. We performed a pooled analysis of these 14 patients, plus our case ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…GISTs account for approximately 4% to 7% of soft tissue sarcomas in the abdominal cavity; 2 EGIST is relatively rare. Since Van Der Aa et al 3 reported the first case of primary prostatic EGIST in 2005, only 14 cases [3][4][5][6][7][8][9][10][11][12][13][14][15][16] in the English language appear in PubMed. We performed a pooled analysis of these 14 patients, plus our case (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation